(untitled) (Comprehensive Journal of Science, 2026)
This study aims to analyze the level of job satisfaction among employees in technical education institutions in Libya and explore its impact on professional performance. The research is grounded in a central hypothesis suggesting a statistically significant relationship between employee satisfaction and productivity. To examine this relationship in depth, the main hypothesis was divided into three sub-hypotheses addressing psychological, organizational, and motivational dimensions, and tested through a descriptive-analytical methodology. Data were collected using questionnaires and interviews administered to a random sample of administrative, financial, and legal staff across four higher technical institutes in Tripoli. The data were analyzed using the T-test to measure the significance of differences in response averages. The results revealed that overall job satisfaction was moderate, with notable variation across its dimensions. A statistically significant relationship was found between job satisfaction (including psychological acceptance, work environment, and incentives/promotions) and job performance. The study also identified organizational shortcomings, such as weak teamwork, lack of active professional unions, and dissatisfaction with incentive mechanisms. Based on these findings, the study recommends improving both the physical and organizational work environment, revising incentive and promotion policies to ensure fairness and transparency, activating teamwork and professional unions, and conducting regular assessments of job satisfaction to sustain performance and foster institutional excellence.